2017
DOI: 10.1108/tqm-08-2013-0096
|View full text |Cite
|
Sign up to set email alerts
|

TQM and academic performance in Iraqi HEIs: associations and mediating effect of KM

Abstract: Purpose The purpose of this paper is to investigate the associations between total quality management (TQM) core elements, knowledge management (KM) processes, and educational organization outcome with respect to academic performance (AP). Design/methodology/approach The study is based on a cross-sectional survey design. The survey was conducted on 87 colleges in Iraqi higher-education institutions (HEIs). Four main hypotheses were developed and tested statistically by applying multivariate data analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 27 publications
2
28
0
6
Order By: Relevance
“…Overall TQM has a significant impact on Malaysian construction project performance. The implication is that TQM is a holistic approach, which should be implemented collectively because each practice is interdependent with the other practices (Zwain, Lim, & Othman, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Overall TQM has a significant impact on Malaysian construction project performance. The implication is that TQM is a holistic approach, which should be implemented collectively because each practice is interdependent with the other practices (Zwain, Lim, & Othman, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To effectively manage the existing competition of rival universities in the marketplace, institutions in the higher education sector need to focus on enhancing the total management practices within their institutes by concentrating on five integral components of total quality management, i.e. tangibles, reliability, empathy, responsiveness, and assurance (Zwain et al 2017). Hanaysha et al (2011) found that the five major elements of TQM, including tangibles, reliability, empathy, responsiveness, and assurance, significantly influence the satisfaction level of the student within higher education institutes.…”
Section: Tqm and Non-financial Performancementioning
confidence: 99%
“…The tangibles aspect of TQM facilitates customers to assess the services provided by the organization before its utilization (Zwain et al, 2017). In the service industry, tangibility is termed as a vital aspect of TQM that influences customer satisfaction largely.…”
Section: Tangibles and Non-financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…These CFSs been recognized as the important CSFs for implementation of TQM in the service industry such as hospitality and hotel (Camisón, 1996;Claver-Cortés, Pereira-Moliner, Tarí, & Molina-Azorín, 2008; Pereira-Moliner, Claver-Cortés, Molina-Azorín, & José Tarí, 2012; Wang, K. Y. Chen, & S. C. Chen, 2012). (Sadikoglu & Olcay, 2014); (Akgün, Ince, Imamoglu, Keskin, & Kocoglu, 2014); (Aquilani et al, 2017); (Benavides-Velasco, Quintana-García, & Marchante-Lara, 2014); (Honarpour, Jusoh, & Long, 2017); (Jaca & Psomas, 2015); (Mehralian, Nazari, Nooriparto, & Rasekh, 2017); (Nguyen & Chau, 2017); (Patyal & Koilakuntla, 2017); (Uluskan, Godfrey, & Joines, 2017); (Zwain, Lim, & Othman, 2017) Process management (Sadikoglu & Olcay, 2014); (Akgün et al, 2014); (Aquilani et al, 2017); (Cho, Jung, & Linderman, 2017); (Nguyen & Chau, 2017); (Patyal & Koilakuntla, 2017); (Uluskan et al, 2017); (Zeng, Zhang, Matsui, & Zhao, 2017) Customer focus (Psomas & Jaca, 2016); (Aquilani et al, 2017); (Benavides-Velasco et al, 2014); (Cho et al, 2017); (Honarpour et al, 2017); (Jaca & Psomas, 2015); (Mehralian et al, 2017); (Nguyen & Chau, 2017); (Zwain et al, 2017) Continuous improvement (Wang et al, 2012); (Pereira-Moliner et al, 2012); (Alvarez, Jaca, Viles, & Colomer, 2012); (Abd & Al Manhawy, 2013);…”
Section: Tqm Critical Success Factors In Hospitality Industrymentioning
confidence: 99%